2000
DOI: 10.1177/088307380001500415
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Cerebrospinal Fluid Concentrations of Monoamine-Related Substances Revealed With a Coulochem Electrode Array System

Abstract: The relationship between age and cerebrospinal fluid concentrations of monoamine-related substances, including kynurenine, were investigated using a Coulochem electrode array system, to clarify developmental changes in monoamine-related substances in the human central nervous system. In neurologically normal children, significant inverse correlations with age were observed for the cerebrospinal fluid concentrations of 5-hydroxytryptophan, 5-hydroxyindole-acetic acid, kynurenine, homovanillic acid, 3-methoxy-4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…It is difficult to speculate about mechanisms underlying the finding of heterogeneous development across the subcortical brain, including across hemispheres; however the patterns may relate to the different rates of maturation of the dopaminergic and serotonergic pathways (Casey & Jones, ; Chambers et al ., ; Lambe, Krimer & Goldman‐Rakic, ; Takeuchi, Matsushita, Sakai, Kawano, Yoshimoto & Sawada, ) and the differential distribution of these receptors in the subcortical brain (Brown, Crane & Goldman, ). For example, the amygdala, a structure that is both functionally associated with serotinergic activity (Hariri, Mattay, Tessitore, Kolachana, Fera, Goldman, Egan & Weinberger, ) and has nuclei that are more densely populated with serotinergic receptors relative to the other regions described in this study (Pazos, Probst & Palacios, ), did not show developmental change.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to speculate about mechanisms underlying the finding of heterogeneous development across the subcortical brain, including across hemispheres; however the patterns may relate to the different rates of maturation of the dopaminergic and serotonergic pathways (Casey & Jones, ; Chambers et al ., ; Lambe, Krimer & Goldman‐Rakic, ; Takeuchi, Matsushita, Sakai, Kawano, Yoshimoto & Sawada, ) and the differential distribution of these receptors in the subcortical brain (Brown, Crane & Goldman, ). For example, the amygdala, a structure that is both functionally associated with serotinergic activity (Hariri, Mattay, Tessitore, Kolachana, Fera, Goldman, Egan & Weinberger, ) and has nuclei that are more densely populated with serotinergic receptors relative to the other regions described in this study (Pazos, Probst & Palacios, ), did not show developmental change.…”
Section: Discussionmentioning
confidence: 99%
“…The under-specialized reward system may be limited in adolescence in the ability to properly assess the valence (rewards and punishment) and value of incentives. Additionally, during adolescence there is greater activity in dopamine systems that surpasses that of inhibitory 5-HT systems resulting in a potential imbalance in reward and suppression mechanisms (Andersen, 2005; Chambers et al, 2003; Lambe, Krimer, & Goldman-Rakic, 2000; Takeuchi et al, 2000). The effects of reward on the cognitive control of eye movements could provide a model to test incentive processing in development and psychopathology.…”
Section: Development Of Voluntary Control Of Eye Movementsmentioning
confidence: 99%
“…The density of dopamine transporters, which function to remove DA from the synapse, has also been shown to peak during adolescence in the striatum (Meng et al, 1999). Furthermore, evidence indicates that during adolescence, there is relatively greater activity in dopamine systems than in inhibitory serotonin (5-HT) systems, potentially resulting in an imbalance in reward (DA-mediated) and suppression (5-HT-mediated) mechanisms (Takeuchi et al, 2000; Lambe et al, 2000; Ernst et al, 2006; Spear, 2000). In mesocortical pathways, non-human primate work has shown that DA inputs to prefrontal cortex (PFC) peak in adolescence (Rosenberg and Lewis, 1994; Rosenberg and Lewis, 1995; Spear, 2000).…”
Section: Brain Maturation During Adolescencementioning
confidence: 99%